Consumption of Food Components of the Mediterranean Diet Decreases the Risk of Breast Cancer in the Makkah Region, Saudi Arabia: A Case-Control Study - Azzeh, Firas S.; Hasanain, Deena M.; Qadhi, Alaa H.; Ghafouri, Khloud J.; Azhar, Wedad F.; Ghaith, Mazen M.; Aldairi, Abdullah F.; Almasmoum, Hussain A.; Assaggaf, Hamza M.; Alhussain, Maha H.; Alghamdi, Ahmad A.; Habibullah, Mahmoud M.; et al. (Frontiers in Nutrition, 2022)
Background Breast cancer is one of the leading causes of death worldwide, it affects both men and women. In Saudi Arabia, breast cancer has been the most prevalent type of cancer in women, for the past few years. Dietary habits and cultural beliefs vary according to region, and further studies are required to demonstrate the relationship between these dietary habits and cultural beliefs and the risk of developing breast cancer. This study is aimed to discover the relationship between preventive dietary factors of the Mediterranean diet and rates of breast cancer among postmenopausal women in the Makkah region of Saudi Arabia. Methods A case-control study was conducted in King Abdulla Medical City Hospital, Makkah, Saudi Arabia and included 432 Saudi female participants: 218 in the control group and 214 breast cancer patients. All participants were postmenopausal, around the same age, and all were ethnically Arab Saudis. Data were obtained using a self-administered validated questionnaire. Results Study results showed that a diet that includes 1–2 servings of legumes weekly, 1–5 servings of fish weekly, 1–5 servings of dairy products daily, 3–5 servings of fruits and vegetables daily, and more than one cup of black tea and coffee per day significantly (p < 0.05) reduces the risk of breast cancer. Conclusion This study demonstrates that consuming a Mediterranean diet, which includes legumes, fish, fruits and vegetables, black tea, coffee, and low intake of dairy products, works as a preventive factor against breast cancer in postmenopausal females from the Makkah region.